THE DIFFERENCES OF STUDENTS’ LEARNING ACHIVEMENT TAUGHT SOMATIC, AUDIOTORYTORY, VISUAL, AND INTELLECTUAL (SAVI) LEARNING MODEL AND DIRECTT INSTRUCTION (DI) LEARNING MODEL ON SETS TOPICS IN VII GRADE AT SMP N 1 BINJAI ACADEMIC YEAR 2014/2015 - Evridya . Rizki; Pargaulan . Siagian (INSPIRATIF : JURNAL PENDIDIKAN MATEMATIKA, 2015)
th: 0px; "> AbstractThis research is experiment. The purpose of this research was to know the differences of students’learning achievement between SAVI class and Direct Instructional class in mathematical learningprocess on sets topic at SMP Negeri 1 Binjai. The population of this research was all VII gradestudents of SMP Negeri 1 Binjai which consists of 9 classes, whereas the sample consist of 2 classes,they are VII-4 as experimental class consists of 30 students and VII-5 as control class consists of 30students. Experimental class used SAVI, whereas control class used direct instruction learning model.Collecting data technique of this research was pre-test that given in the end of learning process inexperimental class and control class. The type of this test is essay test. Before doing hypothesis test, itwould be done normality test and homogeneity test beforehand. From the result of those tests, samplewas taken from normal distribution and homogeneous population. From the data analysis ofexperimental class by using t-test with significance level α = 0.05, it was obtained that tcalculated(8.372) > ttable ( 1.671) then H0 is rejected and Ha is accepted.So, it can be concluded that, there is thedifference of students’ learning achievement from SAVI class between Direct Instruction class and theimprovement of students’ learning achievement in SAVI class is better than students’ learningachievement in Direct Instruction class. On other words, SAVI learning model can improve thestudents’ learning achievement in grade VII on the set topics at SMP N 1 Binjai academic years2014/2015.Keywords : Learning Achievement, Set Topics, SAVI Learning Model, Junior High School, Binjai,North Sumatra